2020
DOI: 10.3390/biom10030409
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Pharmacokinetic Interactions of 24 Colonic Flavonoid Metabolites with Human Serum Albumin and Cytochrome P450 Enzymes

Abstract: Flavonoids are abundant polyphenols in nature. They are extensively biotransformed in enterocytes and hepatocytes, where conjugated (methyl, sulfate, and glucuronide) metabolites are formed. However, bacterial microflora in the human intestines also metabolize flavonoids, resulting in the production of smaller phenolic fragments (e.g., hydroxybenzoic, hydroxyacetic and hydroxycinnamic acids, and hydroxybenzenes). Despite the fact that several colonic metabolites appear in the circulation at high concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 74 publications
(124 reference statements)
0
9
0
Order By: Relevance
“…Inhibitory effects of chrysin, C7S, and C7G on CYP2C9 (Mohos et al, 2020), CYP2C19 (Fliszár-Nyúl et al, 2019), and CYP3A4 (Mohos et al, 2018b) enzymes were investigated as has been reported, without modifications. Inhibition of CYP2D6 enzyme by chrysin and its conjugates was examined based on their effects on CYP2D6-catalyzed O-demethylation of dextromethorphan.…”
Section: Pharmacokinetic Interactions Of Chrysin and Its Conjugatesmentioning
confidence: 99%
“…Inhibitory effects of chrysin, C7S, and C7G on CYP2C9 (Mohos et al, 2020), CYP2C19 (Fliszár-Nyúl et al, 2019), and CYP3A4 (Mohos et al, 2018b) enzymes were investigated as has been reported, without modifications. Inhibition of CYP2D6 enzyme by chrysin and its conjugates was examined based on their effects on CYP2D6-catalyzed O-demethylation of dextromethorphan.…”
Section: Pharmacokinetic Interactions Of Chrysin and Its Conjugatesmentioning
confidence: 99%
“…The potential inhibitory effects of AOH on CYP2C9, 2C19, 2D6, and 3A4 enzymes were tested in vitro employing CypExpress human kits, using the substrates recommended by the U.S. Food and Drug Administration (FDA; ; accessed on 19 December 2022) (diclofenac, S -mephenytoin, dextromethorphan, and testosterone, respectively). The impacts of increasing concentrations of AOH (0.00, 0.05, 0.50, 2.0, 5.0, 10, 25, 30, and 50 μM) were examined on diclofenac 4′-hydroxylation (CYP2C9) [ 25 ], S -mephenytoin 4-hydroxylation (CYP2C19) [ 26 ], dextromethorphan demethylation (CYP2D6) [ 20 ], and testosterone 6β-hydroxylation (CYP3A4) [ 27 ] as described previously, without modifications. In these assays, the substrates and products were quantified by HPLC-UV [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…To illustrate, phenolic fragments (e.g., hydroxybenzoic, hydroxyacetic and hydroxycinnamic acids, and hydroxybenzenes) are produced from flavonoids by bacterial microflora. Some of these metabolites form stable complexes with albumin in vitro [41] though appear to have limited potential to displace drugs from binding sites. Finally, several "uremic toxins" that are dependent on the presence of gut microflora, such as indoxyl sulfate, hippuric acid, and phenylacetic acid, are also highly bound in plasma to albumin [42,43].…”
Section: Volume Of Distributionmentioning
confidence: 99%